Study on the influence of the mass eccentric wheelset on the wheel polygonal wear of high-speed trains - Xiaonan Zhao; Songhua Zhao; Pingping He; Feng Yu (PLoS ONE, 2026)
In the paper, the finite element model of the wheelset-track system is established, and the explicit transient dynamic analysis method is used to study the dynamic response. The research results show that when the mass eccentric wheelset rolls on the rails, the eccentric mass will increase the wheel-rail contact force, and the peak changes of the vertical contact force are more than those of the lateral force peak changes. As the speed increases, the mass eccentric wheelset will increase the vertical vibration energy of the wheelset-track system and make the vibration energy in the middle-high frequency range increase significantly. When the speed v = 300 km/h, the corresponding vibration frequency f = 534.82 Hz becomes very prominent, which is close to the passing frequency of high-order wheel polygonal wear. At the same time, with the increase of the dynamic unbalance U , the overall vibration energy of the wheelset-track system presents an increasing trend, but it has little effect on the main frequency of unstable vibration. Finally, the larger the eccentric phase difference of the wheelset mass, the more the main frequency of unstable vibration exists in the middle-high frequency region, which is easy to cause high-order wheel polygonal wear.